2022
DOI: 10.3390/s22166193
|View full text |Cite
|
Sign up to set email alerts
|

Data Augmentation for Deep-Learning-Based Multiclass Structural Damage Detection Using Limited Information

Abstract: The deterioration of infrastructure’s health has become more predominant on a global scale during the 21st century. Aging infrastructure as well as those structures damaged by natural disasters have prompted the research community to improve state-of-the-art methodologies for conducting Structural Health Monitoring (SHM). The necessity for efficient SHM arises from the hazards damaged infrastructure imposes, often resulting in structural collapse, leading to economic loss and human fatalities. Furthermore, day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In DL, the learners show reliable performance for noisy datasets and hence raw sensor data can be directly fed into the classifier without pre-processing [69,70]. However, the major limitation of DL is its requirement for a large number of training data which can be somehow obtained through different augmentation techniques [71][72][73][74][75]. However, this approach will not be viable if the training dataset is too short to represent the basic distinguishable characteristics in the data.…”
Section: Damage Identificationmentioning
confidence: 99%
“…In DL, the learners show reliable performance for noisy datasets and hence raw sensor data can be directly fed into the classifier without pre-processing [69,70]. However, the major limitation of DL is its requirement for a large number of training data which can be somehow obtained through different augmentation techniques [71][72][73][74][75]. However, this approach will not be viable if the training dataset is too short to represent the basic distinguishable characteristics in the data.…”
Section: Damage Identificationmentioning
confidence: 99%
“…GANbased data augmentation proves valuable in enhancing model performance across various fields, especially in situations where data acquisition is challenging. Dunphy et al [19] validated the use of synthetically generated images from GANs for multi-class damage detection on concrete surfaces. Their research indicated that the average classification performance for hybrid datasets decreased by approximately 10.6% and 7.4% for validation and testing datasets, respectively, when compared to models trained solely on real samples.…”
Section: Data Augmentationmentioning
confidence: 99%
“…While common data augmentation methods like random flipping, rotating, and cropping have demonstrated their ability to bolster the resilience of trained DNNs, they possess limitations in encapsulating the authentic diversity seen in real-world structures. This includes the variations in building attributes such as size, shape, and color, consequently curbing these methods' efficacy [18][19][20]. In response to this issue, researchers have introduced innovative data augmentation strategies that leverage synthetic images-either generated by computers or data-driven [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the training of CNNs requires many defect samples and necessitates additional manpower for defect labeling, which makes it difficult to import deep learning technology into actual production lines. Although many data augmentation methods have been proposed thus far [ 11 , 12 , 13 , 14 ], the application of CNNs in industrial testing remains limited.…”
Section: Introductionmentioning
confidence: 99%